Comparative Perspectives to Advertising by Lawyers in Nigeria - Bukola, Akinola O.; (Mrs), Ebun L. Effiong (IJRDO - Journal of Business Management, 2017)
This paper analyzes the extent to which a legal practitioner can advertise his trade in view of global initiatives and contemporary challenges in the legal profession. Part E of the Rules of Professional Conduct for Legal Profession 2007 was critically examined in this paper vis a vis similar provisions in selected jurisdictions. The paper welcomes new innovations and possible amendments of the Rules of Professional for Conduct for Legal Practitioners 2007 in line with international best practices. The paper further makes comparative analysis of lawyer advertising in the USA, UK, Canada and South Africa. The paper makes recommendations on the need to improve legal marketing by Nigerian lawyers within the ambit of an amended Rules of Professional Conduct